TAVI for Pure Non-calcified Aortic Regurgitation Using a Self-Expandable Transcatheter Heart Valve - Schneeberger, Yvonne; Seiffert, Moritz; Schaefer, Andreas; Bhadra, Oliver D.; Schofer, Niklas; Pecha, Simon; Westermann, Dirk; Blankenberg, Stefan; Reichenspurner, Hermann; Conradi, Lenard (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Transcatheter aortic valve implantation (TAVI) is routinely performed in patients with severe aortic stenosis (AS). For patients with pure non-calcified aortic regurgitation (AR) who are not suitable for open heart surgery no clear recommendations exist and use of TAVI has been largely off-label. We herein report a series of patients treated with the self-expandable AcurateNeo and Neo2 (Boston Scientific Co., Marlborough, MS, USA) transcatheter heart valve (THV) for pure AR. Methods: Between 05/2017 and 03/2021, 9 patients (88.8% female, 74.4 ± 7.1 years, logEuroSCORE II 5.5 ± 3.6%, STS PROM 6.2 ± 3.0%) received transfemoral (TF) TAVI for pure non-calcified AR following an adjusted valve sizing algorithm. Data were retrospectively analyzed according to updated Valve Academic Research Consortium (VARC-2) definitions. Results: Device success was 100%. Early safety was 77.7% (7/10), due to two (22.2%) cases of acute kidney injury. 30-day mortality was 0%, in seven (77.7%) patients no or trace paravalvular leakage (PVL) was seen and mild PVL in two (22.2%) patients at 30-day follow-up. No permanent pacemaker (PPM) was required during 30-day follow-up. Conclusion: In this series of selected patients using the Acurate neo THV for pure non-calcified AR, safety and efficacy were demonstrated. 30-day mortality as well as PPM implantation and PVL rates showed excellent results in this high-risk patient cohort. These results will have to be confirmed in larger patient cohorts.